Visible light-enabled sp3-C-H functionalization with chloro- and bromoalkynes: chemoselective route to vinylchlorides or alkynes - Adak, Tapas; Hoffmann, Marvin; Witzel, Sina; Rudolph, Matthias; Dreuw, Andreas; Hashmi, A. Stephen K. (Chemistry - a European journal, 2020)
An unprecedented direct atom-economic chemo- and regioselective hydroalkylation of chloroalkynes and an sp3-C−H alkynylation of bromoalkynes was achieved. The reaction partners are unfunctionalized ethers, alcohols, amides, and even non-activated hydrocarbons. We found that a household fluorescent bulb was able to excite a diaryl ketone, which then selectively abstracts a H-atom from an sp3-C−H bond. The product of a formal alkyne insertion into the sp3-C−H bond was obtained with chloroalkynes, providing valuable vinyl chlorides. The photo-organocatalytic hydrogen atom transfer strategy gives rise to a broad range of diversely functionalized olefins. When bromoalkynes are applied in the presence of a base, a chemoselectivity switch to an alkynylation is observed. This reaction can even be performed for the alkynylation of unactivated sp3-C−H bonds, in this case with a preference of the more substituted carbon. Accompanying quantum chemical calculations indicate a vinyl radical intermediate with pronounced linear coordination of the carbon radical center, thus enabling the formation of both diastereoisomers after H-atom abstraction, suggesting that the (Z)-diastereoisomer is preferred, which supports the experimentally observed (E/Z)-distribution.